Strategi Komunikasi Public Relations PT.Telkom Indonesia TBK di Jakarta dalam Menjaga Citra Perusahaan - Ramadhan Putra Ardianto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Telkomunikasi or what we usually know as Telkom is a company operating in the communications sector and is currently the largest telecommunications company in Indonesia, not only PT. Telkom is also the sixth largest company in the world. Public Relations is an important part of maintaining a company's image. This thesis discusses the strategy of PT. Telkom Indonesia Tbk in Jakarta in maintaining the company's image. There are 1 main problems contained in it, namely: what is the public relations strategy of PT. Telkom Indonesia Tbk in Jakarta in maintaining the company's image? This type of research is descriptive qualitative. With a communication research approach, using data collection techniques through interviews, observation and documentation. Meanwhile, data processing and analysis techniques are carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. The research results can be concluded as follows: Public relations strategy at PT. Telkom Indonesia in maintaining its corporate image, namely: (1) arranging media relations/media partnership activities. (2) establishing good/harmonious relationships within the company both within the company environment (internal public) and with the environment outside the company (external public) Business carried out by PT. Telkom Indonesia, Tbk in maintaining the company's image, namely (1) maximizing good and excellent service to consumers, channeling concern through the help of corporate social responsibility (CSR). (2) strengthening employee duties, in order to achieve the company's vision and mission in maintaining the company's image as part of public relations duties. From the results of this research, strategies for activities carried out in a company must understand the importance of the techniques used as strategies, especially public relations strategies to help carry out company activities to achieve goals or vision and mission.